Laboratory Evaluation of a Rapid IgG4 Antibody Test (BLF Rapid™) for Bancroftian Filariasis - Noordin, Rahmah; Yunus, Muhammad Hafiznur; Robinson, Keri; Won, Kimberly Y.; Babu, Subash; Fischer, Peter U.; Hisam, Shamilah; Mahmud, Rohela (American Society of Tropical Medicine and Hygiene, 2018)
At the end phase of the Global Programme to Eliminate Lymphatic Filariasis, antibody testing may have a role in decision-making for bancroftian filariasis–endemic areas. This study evaluated the diagnostic performance of BLF Rapid ™ , a prototype immunochromatographic IgG4-based test using BmSXP recombinant protein, for detection of bancroftian filariasis. The test was evaluated using 258 serum samples, comprising 96 samples tested at Universiti Sains Malaysia (in-house) and 162 samples tested independently at three international laboratories in the USA and India, and two laboratories in Malaysia. The independent testing involved 99 samples from Wuchereria bancrofti microfilaria or antigen positive individuals and 63 samples from people who were healthy or had other infections. The in-house evaluation showed 100% diagnostic sensitivity and specificity. The independent evaluations showed a diagnostic sensitivity of 84–100% and 100% specificity (excluding non-lymphatic filarial infections). BLF Rapid has potential as a surveillance diagnostic tool to make “Transmission Assessment Survey”–stopping decisions and conduct post-elimination surveillance.